A POET HAS A POET FOR THE POET… BETWEEN THE ARTISTIC FREEDOM AND THE INTENTION OF AN AUTHOR - Tomczak, Daniel (Porównania, 2012)
Literary translation is an ungrateful art as it requires artistry and it doesn’t offer freedom. It lags behind in the shadow of literature underestimated as an element of culture creation, and gains relatively small profits, with the exclusion of lucrative blockbusters. The present article is devoted to two German poets, Durs Grünbein and Thomas Rosenlöcher, as well as the translation of their writings into Polish that have been carried out by Jakub Ekier, a poet and a Warsaw scholar of German. Apart from a discussion of the selected poems and a few theories of translation, the main subject of this article is a detailed analysis of the translation work of Jakub Ekier which will address a number of questions, among others: Is the translating enterprise of Ekier a rendition, translation or maybe Nachdichtung in the typology of Karl Dedecius? How does Ekier treat the issue of the translation as an interpretation and the topic of loyalty to the original? Likewise, the aim of this study is to examine the strategies of translation, methods and techniques used by the translator.